2015
DOI: 10.5530/pc.2015.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition and Potential Genotoxic effects of Important Egyptian Medicinal Plants

Abstract: Introduction: We performed a phytochemical analysis and investigated the potential genotoxic properties of ten different methanol extracts of plants that are frequently used in Egypt for medicinal purposes. Such studies are important because these plants were never thoroughly investigated with respect to their possible potential sideeffects and risks for humans. Materials and Methods: In this study we used the bacterial Vitotox test and alkaline comet assay in human C3A cells to estimate their genotoxic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The neutral red uptake (NRU) assay is a cytotoxicity assay that measures the neutral red dye uptake by the lysosomes. [19] The assay was performed on C3A cells as described by Rashed et al [20] After 24 h exposure of cells to six different concentrations of plant extracts, the cells were washed and treated with neutral red dye for 3 h at 37°C. Thereafter, the intracellular bound dye was extracted from the cells and the optical density at 540 nm was measured.…”
Section: Neutral Red Uptake Assaymentioning
confidence: 99%
“…The neutral red uptake (NRU) assay is a cytotoxicity assay that measures the neutral red dye uptake by the lysosomes. [19] The assay was performed on C3A cells as described by Rashed et al [20] After 24 h exposure of cells to six different concentrations of plant extracts, the cells were washed and treated with neutral red dye for 3 h at 37°C. Thereafter, the intracellular bound dye was extracted from the cells and the optical density at 540 nm was measured.…”
Section: Neutral Red Uptake Assaymentioning
confidence: 99%
“…Also, qualitative preliminary phytochemical analysis of F. vasta leaves, undertaken by Rashed with coauthors (2015), revealed the presence of carbohydrates, tannins, flavonoids, coumarins, and triterpenes [22]. Moreover, various phytoconstituents such as β-sitosterol, stigmasterol, lupeol, ursolic acid, and some flavonoids were isolated and identified from F. vasta aerial parts [23].…”
Section: A B Fig 1 Specimen Of Ficus Vasta Cultivated At Botanic Gmentioning
confidence: 99%
“…The leaves of F. vasta are traditionally used for the treatment of rheumatisms, pains and intestinal worms [22].…”
mentioning
confidence: 99%
“…However, many medicinal plants and THPs have been identified as genotoxic and mutagenic. For that reason, it is imperative to investigate the potentially toxic‐genetics effects of plants used in traditional medicine (EMA ; Rashed et al ; Sponchiado et al ). According to Klapacz and Gollapudi (), the genotoxicity refers to deleterious effects to genetic material that cover both transmissible outcomes and endpoints that themselves are not transmissible.…”
Section: Introductionmentioning
confidence: 99%